2013
DOI: 10.3892/mco.2013.149
|View full text |Cite
|
Sign up to set email alerts
|

Serum thymidine kinase 1 levels predict cancer-free survival following neoadjuvant, surgical and adjuvant treatment of patients with locally advanced breast cancer

Abstract: In this study, the use of serum thymidine kinase 1 protein (STK1p) concentration for the prognosis of the overall survival of patients with locally advanced breast cancer (n=51) following routine treatment (neoadjuvant treatment, surgery and chemotherapy) was investigated. The patients were followed up for 44 months and the STK1p values were determined by a high-sensitivity enhanced chemiluminescence (ECL) dot blot assay. The variables investigated in relation to metastasis and survival were STK1p, clinical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 24 publications
2
13
0
2
Order By: Relevance
“…[42] при мониторинге пациен-тов с местно-распространенным РМЖ (медиана наблюде-ния 44 мес) установили, что при уровне ТК-1 >2,0 пмоль/л через 6 мес после хирургического лечения степень риска развития метастазов возрастала в 11-12 раз в сравнении с группой пациентов с уровнем ТК-1 <2,0 пмоль/л. Авторы предложили использовать этот уровень для дискримина-ции больных с местно-распространенным РМЖ на под-группы с различным прогнозом и учитывать его при инди-видуализации тактики лечения [42]. Z. H. Huang и соавт.…”
Section: тк-1 при солидных опухоляхunclassified
“…[42] при мониторинге пациен-тов с местно-распространенным РМЖ (медиана наблюде-ния 44 мес) установили, что при уровне ТК-1 >2,0 пмоль/л через 6 мес после хирургического лечения степень риска развития метастазов возрастала в 11-12 раз в сравнении с группой пациентов с уровнем ТК-1 <2,0 пмоль/л. Авторы предложили использовать этот уровень для дискримина-ции больных с местно-распространенным РМЖ на под-группы с различным прогнозом и учитывать его при инди-видуализации тактики лечения [42]. Z. H. Huang и соавт.…”
Section: тк-1 при солидных опухоляхunclassified
“…The TK1 antibody inhibited the catalytic activity of the enzyme [9]. In native Western blot analysis of TK1 in serum (STK1) from pre-treated patients with gastric cancer [9,10], non-Hodgkin's lymphoma [11], and breast cancer [12], one single band corresponding to human TK1 was obtained, demonstrating the high specificity of the anti-TK1 IgY antibody. The weak TK1 band found in serum of healthy individuals showed the high sensitivity of the IgY TK1 antibody in serum of cancer patients [9][10][11][12].…”
Section: Introductionmentioning
confidence: 98%
“…In native Western blot analysis of TK1 in serum (STK1) from pre-treated patients with gastric cancer [9,10], non-Hodgkin's lymphoma [11], and breast cancer [12], one single band corresponding to human TK1 was obtained, demonstrating the high specificity of the anti-TK1 IgY antibody. The weak TK1 band found in serum of healthy individuals showed the high sensitivity of the IgY TK1 antibody in serum of cancer patients [9][10][11][12]. This IgY TK1 antibody has been used in the clinical setting in health screening and oncology application for more than a decade [13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…21 A comparison between TK1 and Ki-67 showed that Ki-67 was not an independent prognostic factor for survival in patients with cervical carcinomas or lung pT1 adenocarcinoma. 18,20 It was also demonstrated that serum TK1 was an independent prognostic factor for the risk of recurrence in breast carcinoma 22,23 and for survival rates in breast carcinoma, 24 gastric carcinoma, 25 and Hodgkin's lymphoma. 26 In this study, we investigated whether TK1 expression could serve as a prognostic factor for relapse and overall survival in serous ovarian adenocarcinoma patients and compared these results with those for Ki-67.…”
Section: Introductionmentioning
confidence: 99%